Determinasi Struktur Modal pada Bank Umum Syariah di Indonesia: Peran Pertumbuhan, Profitabilitas, dan Tangibilitas - Asti Adhariyah Febriyanti; Sri Rokhlinasari; Nining Wahyuningsih (CIEBER: Contemporary Islamic Economic and Business Review, 2026)
This research was conducted to find out whether or not there is an influence of growth rate, profitability and tangibility on the capital structure of Sharia Commercial Banks in Indonesia for the 2020-2023 period. This research is quantitative with the sample used is 10 Islamic commercial banks in Indonesia in the period 2020-2023 which have the highest assets in that period. The data collection technique uses secondary data obtained from financial reports from each related bank website according to the period used. The software used in the data processing process of this research is IBM SPSS Statistic 26. This research uses independent variables in the form of growth rate (X1), profitability (X2), tangibility (X3) and uses the dependent variable, namely capital structure (Y). The result of testing partially growth rate variable has insignificant effect on capital structure with significance value 0.805 (>0.05) with positive direction. Profitability variable partially has significant effect on capital structure with significance value 0.043 (<0.05) with negative direction. Tangibility variable partially has insignificant influence on capital structure with significance value 0.241 (>0.05) with positive direction. Simultaneous testing between the dependent variable and the independent variable produces a singnification level of 0.128 (>0.05) which means that the growth rate, profitability and tangibility have no significant effect on capital structure.